Especies leñosas de la Sierra de los Cuchumatanes y de la Cadena Volcánica, Guatemala - Islebe, Gerald A.; Cleef, Antoine M.; Velazquez, Alejandro (Instituto de Ecología, A.C., 1994)
The present checklist reports 112 woody plant species found in the Sierra de los Cuchumatanes and the Volcanic Chain of Guatemala (elev. 3000-4000 m). These 112 species belong to 39 families and 63 genera. The best represented families are Asteraceae and Ericaceae.